PERAN DEWAN PASTORAL STASI TERHADAP PARTISIPASI UMAT DALAM IBADAT SABDA HARI MINGGU - Ona Sastri Lumban Tobing (STP St. Bonaventura Medan, 2019)
Sunday's celebration of the word of worship is a celebration for all Catholics. In this celebration, all the people took a real part in the form of presence and duty. The participation of the congregation in their duties, for example as worship leaders. Lector. psalmist, collectant, conductor and so on. The community's participation cannot be separated from the role of the station's pastoral council. The DPS is an extension of the DPP and the parish priest whose function is to help direct the congregation to be involved in various pastoral activities in the fields of kerygma, liturgy, diakonia, coinsonia and martyria. This research uses a qualitative approach with observation, interview and documentation techniques. In this research, it appears that DPS has played a good role in increasing congregational participation in the celebration of the prayer service at the station